Alpha Decay Preformation Factors for Even–Even 280–316116 Superheavy Isotopes - Alsaif, N.A.M.; Radiman, S.; Yahaya, R.; Ahmed, S.M.S. (Springer Verlag (Germany), 2016)
The success of the cluster formation model (CFM) in deriving an energy-dependent formula for the preformation factors of heavy nuclei has motivated us to expand this approach to the superheavy isotopes (SHI). In this paper, the alpha-cluster formation (preformation factor) behavior inside the parent nuclei of SHI with atomic number Z = 116 and neutron numbers 164 ≤ N ≤ 200 is determined using the alpha preformation formula contained within the CFM. The cluster formation energy of the alpha particles and the total energy of the parent nuclei are calculated on the basis of the various binding energies. Our results clearly show that the CFM remains valid for superheavy nuclei (SHN). In addition, our calculations reveal that the alpha clustering mechanism and formation probability in 280–316116 even–even SHI are similar to those of even–even heavy nuclei in a general sense.